ANALISIS USAHA PENGOLAHAN ABON IKAN KAMPUNG TELUK SULAIMAN KECAMATAN BIDUK-BIDUK KABUPATEN BERAU - Ardiansyah; Muhammad Syafril; Wahyu Fahrizal (2339-1324, 2021)
This study aims to measure the level of income and the feasibility of the shredded fish processing business. Data collection in the field was carried out from January 2020 to April 2020 in Teluk Sulaiman village. The sampling method used the census method with all members of the population as respondents. namely 15 processors. Data analysis methods used are income analysis and business feasibility analysis with indicators of revenue-cost ratio (R / C). Break Even Point (BEP). Payback Period (PP). and return on investment (ROI). The results showed that the shredded fish processing business in Teluk Sulaiman Village generated an average income of IDR 1.619.025 per month per processor. The shredded fish processing business is feasible to be implemented with an R / C value of 2.2. BEP conditions under actual conditions. a Payback period of 1.2 years. and an ROI value of 86.2. Problems in the shredded fish processing business are that the raw material for shredded fish is not available throughout the year. limited business capital. and marketing is still local in nature.